Optic nerve head astrocytes contribute to vascular associated effects - Dong, Yanmin; Fu, Yue; Qian, Xiaobing; Lin, Leilei; Yuan, Yongguang; Li, Yujie; Shao, Wanwen; Gao, Qianying (Frontiers in Medicine, 2022)
Purpose This study was conducted in order to test the expression of vasoactive substances within rat lamina cribrosa (LC) and optic nerve head (ONH) astrocytes, so as to investigate the role and potential mechanism of ONH astrocytes in vascular associated effects. Methods LC tissue sections and primary cultured ONH astrocytes were obtained from adult SD rats. Immunofluorescent staining was then used to detect the expression of vasoactive substances. Hyperoxia exposure was carried out both in vivo and in vitro, after which NO levels in LC tissue and cell supernatant were detected. The variations of protein and gene expression associated with vasoactive substances were subsequently tested. ONH astrocytes and vascular smooth muscle cells (VSMCs) were then incubated in a direct co-culture manner. Morphological parameters of VSMCs were finally analyzed in order to evaluate cell contraction. Results Endothelin-1 (ET-1), nitric oxide synthase (NOS) and renin-angiotensin system (RAS) were detected in both LC tissue and ONH astrocytes. Retinal vessel diameter was found obviously decreased following hyperoxia exposure. Moreover, hyperoxia inhibited NO production both in vivo and in vitro. ET-1 and RAS elements were observed to be upregulated, whereas NOS was downregulated. In ONH astrocytes and VSMCs co-culture system, the length-to-width ratio of VSMCs was shown to significantly increase on days 3 and 7 in hyperoxia compared with normoxia. Conclusions There is an abundance of expression of vasoactive substances within LC tissue and ONH astrocytes, indicating that LC, especially ONH astrocytes, may play an important role in vascular associated effects. The contractile response of VSMCs in the co-culture system provided direct evidence for the involvement of ONH astrocytes in vascular regulation, which may signify a potentially novel focus for future research.